The Effect of Financial Health Level on Increasing Profitability of Insurance Companies Listed on IDX Period of 2014-2018 - Mohamad Yusak Anshori; Ira Fasila; Ninnasi Muttaqiin (Master of Management, School of Business and Management, Petra Christian University, 2020)
This study was conducted to examine the effect of financial health level of insurance companies on their increasing profitability. It uses profitability as the dependent variable measured by Return on Assets (ROA) and the independent variable is financial health level measured by Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Operational Efficiency Ratio (BOPO). It is quantitative research in which the sample was taken using a purposive sampling method. It uses secondary data collected from the annual financial reports of insurance companies during the 2014-2018 period. There were 10 companies selected and the data were analyzed using multiple linear regression analysis techniques with the Statistical Product and Service Solution (SPSS) program version 23. The results show that three variables— such as Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Net Interest Margin (NIM)— have a positive effect on Return On Assets (ROA). On the contrary, the two variables such as Non-Performing Loans (NPL) and Operational Efficiency Ratio (BOPO) have no effect on Return on Assets (ROA).